Answer :

Given

z^{2} – 12z – 45

Now first find the numbers whose-

Sum = - 12 and

Product = - 45

Required numbers are 15 and 3,

So we get;

z^{2} – 12z – 45

= z^{2} – 15z + 3z - 45

= z(z – 15) + 3(z – 15)

= (z – 15)(z + 3)

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

RELATED QUESTIONS :

6a^{2} – 13a + 6=?

4z^{2} – 8z + 3=?

3 + 23y – 8y^{2}=?

ab – a – b + 1= ?

RS Aggarwal - Mathematicsab – mn + an – bm =?

RS Aggarwal - Mathematicspq^{2} + q(p – 1) – 1 =?

40 + 3x – x^{2}=?

10p^{2} + 11p + 3 = ?

y^{2} + 2y – 3=?

12x^{2} + 60x + 75 = ?